Lightning teeth and Ponari sweat: Folk theories and magical uses of prehistoric stone axes (and adzes) in Island Southeast Asia and the origin of thunderstone beliefs. Issue 1 (2nd January 2018) - Brumm, Adam
Abstract: A popular belief exists in parts of Island Southeast Asia that prehistoric stone axes (and/or adzes) are natural objects generated by lightning. In particular, ancient edge-ground artefacts are widely classified as teeth of the lightning (or thunder) by rural people in Indonesia and the Philippines, and valued for their perceived mystical properties. Such beliefs are strikingly similar to historically known conceptions of stone implements, in particular axes (i.e. thunderstones or thunderbolts), elsewhere in the world, especially in folk traditions of Europe. I consider how these apparently highly arbitrary connections between empirically unrelated phenomena could have arisen among widely separated, and culturally and linguistically unrelated people in our region and further afield. Natural phenomena are identified that can potentially account for the recurring link between these empirical categories. However, the notion of independent development of thunderstone beliefs does not explain their very widespread distribution. I conclude that the lightning teeth concept in Island Southeast Asia may represent a surviving fragment of early (e.g. Neolithic) Austronesian beliefs, with implications for the origin and past history of the thunderstone phenomenon more widely. Moreover, the initial diffusion of this concept into the Austronesian world, perhaps from northern Australia, cannot yet be ruled out.